High rates of gastroesophageal cancers in patients with dyspepsia undergoing upper gastrointestinal endoscopy in Uganda - Mbiine, Ronald; Nakanwagi, Cephas; Kituuka, Olivia (Endoscopy International Open, 2021)
Background and study aims Dyspepsia is the most common presenting symptom in the gastrointestinal clinic of Mulago National Referral hospital. The etiology is essentially not fully described in our patient population. This study was therefore conducted to establish the causes of dyspepsia based on endoscopic diagnosis among patients with dyspepsia seeking care at the National Referral hospital of Uganda.Patients and methods This retrospective study conducted in the endoscopy unit of Mulago hospital reviewed 356 patient endoscopy reports spanning January 2018 to July 2020 with a focus on those with a referral indication of dyspepsia. Age and sex were the independent variables of interest while the endoscopy findings as reported by the endoscopist were the outcome variable of interest. Results Of the 356 endoscopy reports reviewed, 159 met the inclusion criterion of dyspepsia as the indication. Participant mean age was 47.7 years (± 16.53) with the majority (25.79 %) in the fifth decade while the male to female ratio was 1. The majority of patients had organic dyspepsia (90.57 %) while the commonest finding was gastritis 69 (43.4 %). Gastroesophageal cancers represented (18) 11.32 % of all findings. There was a positive association between age > 50 years with gastroesophageal cancers (7.639) as well as age < 50 years and functional dyspepsia (2.794); however, all these were not statistically significant (P = 0.006 and (P = 0.095, respectively). Conclusions Organic/structural dyspepsia comprises over 90 % of investigated dyspepsia with 11 % comprising cancer among patients seeking endoscopy at the National Referral Hospital of Uganda.